2015
DOI: 10.1177/1352458514566666
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MOG antibodies plead against MS diagnosis in an Acquired Demyelinating Syndromes cohort

Abstract: MOG antibodies are strongly skewed towards ADS children that present with an ADEM-like disease onset. The presence of such antibodies pleads against a future diagnosis of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
144
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 32 publications
9
144
1
5
Order By: Relevance
“…These children with a multiphasic disease course often have ADEM followed by one or more ON. 24,26 Similar results have been documented by other groups, 25 indicating that the presence of anti-MOG positivity tested with cell-based assays statistically suggests against a diagnosis of MS. Still, other studies using cell-based assays have found anti-MOG antibodies particularly in children diagnosed with MS younger than 10 years, 27 suggesting an age-dependent presence of MOG antibodies in pediatric MS.…”
Section: Serum Antibodies To Myelin Oligodendro-cyte Glycoprotein (Mog)supporting
confidence: 76%
See 2 more Smart Citations
“…These children with a multiphasic disease course often have ADEM followed by one or more ON. 24,26 Similar results have been documented by other groups, 25 indicating that the presence of anti-MOG positivity tested with cell-based assays statistically suggests against a diagnosis of MS. Still, other studies using cell-based assays have found anti-MOG antibodies particularly in children diagnosed with MS younger than 10 years, 27 suggesting an age-dependent presence of MOG antibodies in pediatric MS.…”
Section: Serum Antibodies To Myelin Oligodendro-cyte Glycoprotein (Mog)supporting
confidence: 76%
“…A Dutch nationwide cohort study on 117 children with ADS showed that patients with ADS with antibodies to MOG more frequently present with a polyfocal disease onset with or without encephalopathy, next to TM (recurrent), ON, or NMO negative for antibodies to aquaporin-4. 24 Children with multiphasic ADS not fulfilling MS diagnostic criteria were likely to be positive (8/11) for anti-MOG antibodies. These children with a multiphasic disease course often have ADEM followed by one or more ON.…”
Section: Serum Antibodies To Myelin Oligodendro-cyte Glycoprotein (Mog)mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Compared to AQP4 IgG-associated disease, CBA seropositivity for MOG IgG appears to be associated with less severe disease, including better resolution and less likelihood to relapse, 44 and may also be associated with a non-MS disease phenotype. 45 A serum antibody binding to KIR4.1 (the ATPsensitive inward rectifying potassium channel found primarily on glial cells) has been reported in 47% of adults with MS as well as in a subset of children with acute CNS demyelination. 46,47 Presence of this antibody was not associated with particular clinical features and its significance is uncertain at this time.…”
Section: Cns-directed Antibodies In Pediatricmentioning
confidence: 99%
“…There is some preliminary evidence suggesting potential pathogenicity. 13,14 Pooled data suggest that 25% of children with acute demyelination have MOG antibodies, and the presence of such anti-MOG antibodies occurs in ADEM, recurrent optic neuritis, in some children with AQP4-negative NMOSD, and less commonly in children experiencing the first attack of MS. 15,16 The spectrum of MOGassociated diseases in childhood needs to be further defined and more research is required to determine diagnostic and therapeutic implications.…”
mentioning
confidence: 99%